2016
DOI: 10.1016/j.ijid.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Study of surveillance data for class B notifiable disease in China from 2005 to 2014

Abstract: Effective surveillance is helpful in gaining a better understanding of the infection behaviour of infectious diseases; this will greatly facilitate disease control and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 15 publications
6
38
1
Order By: Relevance
“…Typhoid cases peaked in the summer, which is in accordance with other studies that have shown increases in typhoid with increases in temperature and rainfall [29]. The China study examining notifiable disease reports also found the greatest typhoid incidence in the summer [19]. …”
Section: Discussionsupporting
confidence: 87%
“…Typhoid cases peaked in the summer, which is in accordance with other studies that have shown increases in typhoid with increases in temperature and rainfall [29]. The China study examining notifiable disease reports also found the greatest typhoid incidence in the summer [19]. …”
Section: Discussionsupporting
confidence: 87%
“…Seasonal patterns are a major cornerstone in understanding subtle but drastic effects of climate change on disease dynamics. 7 22 From the present analysis of surveillance data on China's population, we conclude that rubella, HFMD and diarrhoea most frequently occur in summer, whereas conjunctivitis and typhus are most prevalent during summer and autumn, and hydatid disease incidence peaks in winter. There is no fixed seasonality for influenza incidence, and no obvious seasonality was detected for kala-azar.…”
Section: Discussionmentioning
confidence: 75%
“…Class B includes infectious diseases that might cause epidemics such as tuberculosis, syphilis and viral hepatitis. 8 We reported the incidence of class B notifiable diseases in our previous study, 7 with sexual diseases, viral hepatitis and tuberculosis being population health challenges. 7 Class C includes less severe and less infectious diseases such as hand, foot and mouth disease (HFMD), diarrhoea and influenza.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations